(untitled) (Global Journals of Research in Engineering, 2013)
This paper deals with the implementation of a new low cost five level inverter which converts the 9V DC to 9V AC. Complexity and cost of the system are reduced as compared to other configurations by using only five switches, eight diodes and two capacitors. In the proposed scheme, control circuit is designed using 89C51 microcontroller to produce sinusoidal pulse width modulation(SPWM).The developed system can be operated at very high modulation frequencies of upto 200 KHz producing sustained output. This single-phase five level low cost inverter is developed and tested in power electronics laboratory. The waveforms are recorded and analyzed using Digital Storage Oscilloscope TDS2024B. The proposed scheme is very economic and less complex and the experimental results shows that it has low total harmonic distortion.